Developing the Students’ Ability in Reading Through Speed Reading Technique at the First Year Students of SMKN 1 Watunohu - Muhammad Yunus (Journal of Teaching and Education, 2022)
The aim of this CAR (Classroom Action Research) was to improve first year students’ ability at SMKN 1 Watunohu in speed reading technique. This research consisted of two cycles. The cycle of this research consisted of four steps namely: planning, acting, observing and reflecting on the observation. The subject of the research were 26 students of the first year students of SMKN 1 Watunohu in academic year of 2014/2015. To collect data, the researcher used observation checklist and multiple choice test. The data from the observation and multiple choice test were analyzed to investigate the reading process during the cycles of learning process. As a result, in the cycle 1 the students’ reading ability on speed reading technique could not be improved and could not achieve the minimum level of achievement of reading ability. Meanwhile in the second cycle, students could improve their ability on speed reading technique.